BOVEN DIGOEL DALAM PERGERAKAN NASIONAL INDONESIA, 1926__1942 (Pendidikan Sejarah Bagi Generasi Muda) - Susanto T Handoko (FKIP Universitas Cenderawasih, 2022)
This study aims to describe the relationship between Boven Digoel and the Indonesian National Movement. The method used is historical, they are heuristics, criticizing sources, interpretation and historiography. The result shows that Boven Digoel concentration camp is different from that of Germanyâ€™s Nazy: in Boven Digoel, nobody got harassment. However, it shows a psychological and institutional mistery. Keywords: Boven Digoel, Indonesian National Movement, ConcentrationÂ Camp.